(untitled) (Fiep Bulletin - online, 2014)
A sedentary lifestyle is often increased in all age groups . The growth rates of physical inactivity can directly affect and compromise the health and quality of life not only for adults but also for children and adolescents . Thus this article aims to describe / analyze the level of daily physical activity in the lifestyle of students of a public school in Macapa / AP . The methodology used to qualitative research / quantitative , according to the site survey was conducted in the State School Lauro Chaves located in the city of Macapa / AP . As an instrument for data collection questionnaire was used with 4 closed questions and one open . This study had the audience 68 students from 5th to 8th grade of elementary school , they were divided into two groups with 34 girls and 34 boys aged 11 to 16 years . After analysis of the results was contacted that 21% of boys and 16 % girls perform aerobic exercises , flexibility exercises to realize is that 41 % of boys and 47 % girls and for the exercise of force are boys 38% and 37% girls with a frequency from 0 to 2 days. Already 42 % of boys and 51 % girls perform aerobic exercise , 28 % boys 22 % girls practicing flexibility exercise and 30 % of boys and 28 % girls practice activities related to muscle strength at a sufficient frequency of 3 to 7 days week. About time watching tv , it was found that 40% of girls and 6 % of boys remain in front of the TV for more than 6 hours. On the use of electronic equipment 22 % of girls use more than 6 hours and the boys are at most 15 % between 3 and 7 days. It is necessary to create public actions that make children and teens more active physically.